How to harness the nutrition co-benefits of climate resilient agriculture - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
Support was given to the CCAFS knowledge project with IFAD to produce a publication that describes how to harness the nutrition co-benefits of climate resilient agriculture (The Nutrition Advantage).